Carlen v Drury (1812): The Origins of the Internal Management Debate in Corporate Law. Issue 1 (2nd January 2017) - Barnes, Victoria; Oldham, James
ABSTRACT: The origins of the internal management debate and business judgment rule in Anglo-American corporate law can be traced to the landmark case of Carlen v Drury (1812). Through the use of new manuscript sources and archival material, this article offers a deeper analysis of the case than has previously been available. It reveals a number of allegations omitted by the printed reports. By placing the case within its wider historical context, the article attributes Lord Chancellor Eldon's decision to dismiss the case to external circumstances rather than the particular merits of the shareholders' complaints. It shows that, although Eldon did not intervene in this instance, he was, in fact, willing to interfere in disputes which related to corporate governance issues. We argue that this case should be used with caution as early courts were not as hostile to the thought of exercising judicial power as the outcome in Carlen v Drury may suggest.